DESCRIPTION OF TRIGLYCERIDE LEVELS IN MEN WHO CONSUME ALCOHOLIC BEVERAGES IN BONGOIME VILLAGE,TILONGKABILA DISTRICT, BONE BOLANGOREGENCY, GORONTALO PROVINCE - bagu, meylan; Kadir, Laksmyn; Naim, Rizman (Journal of Health, Technology and Science (JHTS), 2024)
Alcohol consumption is often associated with increased plasma triglyceride concentrations and has relevance to the risk of cardiovascular disease and pancreatitis. Ethanol consumed, as much as 90%, will be metabolized by the body, especially in the liver. Ethanol metabolism in the liver results in an increase in cytosolic and mitochondrial nicotinamide adenine dinucleotide dehydrogenase (NADH), leading to disruption of normal metabolism in the liver. The purpose of this study is to find out the picture of thyrglyceride levels in men who consume alcoholic beverages.The method in this study uses a quantitative approach with a descriptive type of research. The sampling technique in this study uses a purposive sampling technique, assuming the number of samples is 20 samples. Using univariate data analysis techniques.The results of the study showed that in people who consumed alcohol seen from the frequency distribution based on age, at the age of 20-30 years had a thyricide level of (35%), at the age of 31-40 years there was a total (45%), at the age of 41-50 there was a total (10%), and 51-60 a total (10%), the results showed that the most presentation was at the age of 31-40 years with a percentage (45%) based on the results of triglyceride tests in alcohol consumers, Normal results were obtained from 13 respondents and abnormal results for 7 respondents, with an average normal result of 105 mg/dl and an average abnormal result of 231 mg/dl and there was an influence on the number of alcohol consumers with triglyceride levels.